Diagnostic delay, clinical stage, and social class: a hospital based study. Issue 3 (June 1993) - Vineis, P; Fornero, G; Magnino, A; Giacometti, R; Ciccone, G
Abstract : STUDY OBJECTIVE–To measure delay in admission to a large hospital and to study the role of social class and other potential determinants of delay. DESIGN–Interview of a 10% sample of newly diagnosed patients admitted to medical or surgical wards, and all those admitted for external hernia or colon cancer between June 1989 and May 1990. SETTING–The largest hospital in an Italian region of five million inhabitants. SUBJECTS–The study population consisted of 330 patients with a range of different medical and surgical conditions, 83 patients with external hernias, and 97 patients with colon cancers. MEASUREMENTS AND MAIN RESULTS–After patient interview and discharge from hospital, the clinical record was consulted for information on the length of stay and the diagnosis, and in particular for the staging of hernia or colon cancer (according to the protocol of the Jefferson Medical College). Multiple logistic regression was used to estimate odds ratios and 95% confidence intervals. There was an association between advanced disease at hospital admission and the patient's educational level. In each of the three groups of patients, those with the highest educational level had a 30% or lower probability of being admitted to hospital with advanced disease compared with those with the lowest education level (after allowance for sex, age, area of residence, and marital status). CONCLUSION–Lower social class was associated with a more advanced clinical stage of hernia or colon cancer, and with a higher probability of urgent admission to the hospital for a newly diagnosed disease. Delay in seeking care, did not however, seem to explain the social class differentials for disease stage.